Does consumption inequality mirror wealth inequality in the survey of consumer finances? - Brant Abbott; Robin Brace (Queen's University, Department of Economics, 2020)
A method to impute consumption expenditure inequality between wealth groups in the Survey of Consumer Finances is provided, allowing for measurement error that is correlated with income and wealth. Identification is derived from observing food at home and food away from home, which are relative necessities and luxuries, respectively. The gap in expenditure between top and bottom wealth quintiles is estimated to have increased by 50% between 2004 and 2013, indicating that observed increases in wealth inequality have passed through to consumption. Repeating this exercise in the Panel Study of Income Dynamics would lead to a much different conclusion, which is a result of that data not capturing the top of the wealth distribution well.
Keywords: D31; E21; 330; Inequality; Wealth; Income; Consumption